2021
DOI: 10.3390/cells10082076
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Supplementation Promotes Extracellular Matrix and Metabolic Changes in Keratoconus

Abstract: Keratoconus (KC) is a common corneal ectatic disease that affects 1:500–1:2000 people worldwide and is associated with a progressive thinning of the corneal stroma that may lead to severe astigmatism and visual deficits. Riboflavin-mediated collagen crosslinking currently remains the only approved treatment to halt progressive corneal thinning associated with KC by improving the biomechanical properties of the stroma. Treatments designed to increase collagen deposition by resident corneal stromal keratocytes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The peaks intensity of 886 cm −1 and 940 cm −1 , related to tryptophan [ 25 , 33 ] and proline/valine, respectively [ 28 ], were higher in GDCD when compared to the control cornea. Even if these biomolecules are normally present in the cornea [ 42 , 43 ], the increased intensity of both the above peaks in the Raman spectra could be related to polyglutamine aggregates, formed from monomers with different length, and present in amyloid fibrils [ 41 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The peaks intensity of 886 cm −1 and 940 cm −1 , related to tryptophan [ 25 , 33 ] and proline/valine, respectively [ 28 ], were higher in GDCD when compared to the control cornea. Even if these biomolecules are normally present in the cornea [ 42 , 43 ], the increased intensity of both the above peaks in the Raman spectra could be related to polyglutamine aggregates, formed from monomers with different length, and present in amyloid fibrils [ 41 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…One method is to supplement culture media with ascorbic acid (vitamin C), which normally promotes collagen secretion and deposition without promoting myofibroblast differentiation [ 5 , 16 , 33 , 34 , 47 , 81 , 82 ]. This hCF stroma-like 3D model and their self-assembled matrix, which mimics the corneal stroma during development [ 33 , 47 , 83 ], but also useful in investigating other pathologies affecting the corneal stroma, such as keratoconus [ 84 , 85 , 86 ], wound healing [ 33 , 87 ], and diabetes [ 88 , 89 , 90 ]. Collectively, these studies highlight that by increasing ECM dimensionality around hCFs, which can significantly influence cell proliferation and survival, mechano-responses, and their differentiation capacity [ 33 , 47 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the mechanistic effects of arginine on GH secretion in vivo, the role of excess arginine in promoting wound healing may be related to the local effects of GH on cell proliferation and migration, in addition to localized effects of arginine on promoting collagen secretion. A recent study from our group showed that arginine supplementation promoted collagen type I secretion in vitro by primary corneal fibroblasts isolated from KC corneas, even though basal gene expression of arginase, the primary enzyme involved in arginine metabolism, was found to be elevated in these cells [ 108 ]. These studies suggest that exogenous application of key metabolites important in collagen monomer synthesis may serve to promote acute collagen deposition, which has implications in developing therapeutics to promote rapid tissue repair.…”
Section: Roles Of Growth Hormone and Insulin-like Growth Factor In The Corneamentioning
confidence: 99%